Epidemiology of figure skating injuries: A review of the literature - Han, J. S.; Geminiani, E. T.; Micheli, L. J. (Sports Health: A Multidisciplinary Approach, 2018)
Context: As the popularity and technical demands of figure skating increase, so will the number of athletes presenting with sport-related problems. Evidence Acquisition: Searches were performed across PubMed from 1980 to 2017. The keywords searched were skating, skaters, incidence, and injuries. The search was limited to English-language articles and human participants. Relevant articles were cross-referenced. Study Design: Clinical review. Level of Evidence: Level 5. Results: Previous studies suggest an increase in incidence of figure skating injuries from 1982 to 2003. When combining all disciplines of figure skating, there is a similar proportion of acute and overuse injuries. Within disciplines, overuse injuries appear to be more common in singles skating, while acute injuries are more common in pairs skating, ice dancing, and synchronized skating. Lower extremity injuries are more common than upper extremity injuries in all disciplines, and pairs skating accounts for the majority of upper extremity injuries. Ankle sprains are the most common skating injury, and patellar tendinitis is the most common overuse injury across all disciplines. Stress fractures are the most common overuse injury in female singles skaters. Conclusion: The predominance of overuse injuries in singles disciplines reflects their increasing technical difficulty, with more difficult jumps and longer training hours. Partner disciplines are more likely to involve acute injuries and upper extremity injuries due to high-risk throws and lifts. Emphasis should be placed on properly fitting skating boots, intrinsic foot and ankle strengthening, and lower extremity flexibility, which may prevent many of the common lower extremity and back injuries in figure skating.